The mediating role of physical education course interest in the relationship between perceived autonomy support, feedback, and school attachment - Sağın, Ahmet Enes; Yücekaya, Mehmet Akif; Uğraş, Sinan; Mergan, Barış; Temel, Cenk; Duran, Muhsin; Duarte-Mendes, Pedro (Frontiers in Psychology, 2025)
IntroductionStudents’ sense of school attachment is crucial for their academic success and emotional well-being. Previous studies have shown that autonomy-supportive behaviors and constructive feedback from teachers can positively affect students’ motivation and participation, especially in physical education (PE) classes. However, limited research has examined the mediating role of students’ interest in PE in the relationship between teacher support and school attachment. This study investigates the mediating role of physical education course interest in the relationship between perceived autonomy support and perceived teacher feedback and students’ overall school attachment.MethodsA total of 560 middle school students in Türkiye participated in this study. The study utilized validated scales to assess perceived autonomy support, teacher feedback, interest in PE, and school attachment. Structural Equation Modeling (SEM) and mediation analyses were conducted using JASP software, with bootstrap methods applied to test indirect effects.ResultsFindings revealed that both perceived autonomy support and teacher feedback positively and significantly predicted school attachment. Interest in PE was found to mediate the relationship between these variables and school attachment. Specifically, perceived autonomy support and feedback increased students’ interest in PE, which in turn enhanced their sense of attachment to school.ConclusionThe study highlights the crucial role of autonomy-supportive teaching and constructive feedback in strengthening students’ interest in PE and promoting school attachment. Teachers who foster a supportive learning climate can significantly enhance students’ educational engagement and emotional connection to school.